Designing an Industry-Based Mandarin Project-Based Learning Model through Micro-Credentialing and Task-Based Language Teaching to Enhance Business Competence - Domos, Erma; Zulyani, Zulyani; Pratama, Adrian Irnanda (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
Mandarin Chinese proficiency has become increasingly for international business communication, especially given China’s position as global economic power. However, traditional language instruction often falls short in preparing learners for real-world business contexts, where advanced competencies such as negotiation, cross-cultural interaction, and professional communication are required. While Project-Based Learning (PBL) and Task-Based Language Teaching (TBLT) have proven effective in fostering authentic language use, and micro-credentials provide verifiable recognition of workplace skills, there remains a gap in integrating these approaches into a comprehensive, industrybased Mandarin curriculum. To bridge that gap, the present study introduces the Industry-Based Mandarin Language PBL Model that integrates PBL, TaskBased Language Teaching (TBLT), and micro-credentials into business competence development. A quan-qual research design was employed to gather information from students, alumni and industry respondents through questionnaires and needs analyses. Results show a clear demand from the user and employer communities for industry-relevant Mandarin in speaking, writing, negotiation and report preparation, and a preference for practical, task based learning and recognition by micro-credentials. The conceptual model proposed in this study represents an overarching, competency-driven, academia–industry interface that would constitute a sustainable approach in the development of competitive graduates skilled in Chinese (in the form of Mandarin) and business.